Shape and Position of The Hands on The Bicycle Drop Bar Analysis - Rahmawati, Elfina; Ramadhan, Ali; Yanuardi Irfani, Muhammad (Indonesian Journal of Physical Education and Sport Science, 2023)
Study Purpose. Road cycling activities are closely related to the aerodynamics and stability of the bicycle movement when used by the user. Drop bars are one of the elements of a road bike and help control speed movements while driving. Drop bars, or what is commonly known as road bike handlebars, are designed to ride at high speeds without sacrificing bike stability. Materials and methods. The research carried out aims to analyze the shape and position of the hands when riding a bicycle, the results of which can be used to maximize the potential of the bicycle drop bar object. This is because cycling has become a community activity nowadays and the use of drop bars on bicycles is often an option for cycling. By using descriptive qualitative research method the shape of the drop bar can be associated with driving stability. Results. The research was conducted by observing a literature study that describes the shape, position of the user, and speed of the bicycle against the drop bar. The drop bar form is made by adjusting the needs and desires of its users. The shape of the drop bar on a racing bicycle can affect the speed, agility, stability, and direction of the bicycle while riding. Conclusion. The comfort generated by the position of the user's hands on the drop bar while riding has an important role in directing and balancing the bicycle so that it does not fall and maintains a constant speed in other words the bicycle is in a stable state.